Effectiveness of the application of the endogenous-hypoxic breathing technique in the physical training of the qualified field hockey players - Sulyma, A.; Bohuslavska, V.; Furman, Y.; Galan, Y.; Doroshenko, E.; Pityn, M. (Journal of Physical Education and Sport, 2017)
The research is devoted to the study of possibilities of professional field hockey players` physical and functional preparedness improvement on the stage of their individual opportunities maximal realization by applying the endogenous-hypoxic breathing technique. The research represents the results of influence of training sessions with and without normobaric hypoxia and hypercapnia application on physical capacity, the body`s aerobic and anaerobic (lactate and alactic) productivity, the external respiration apparatus function, as well as blood pressure recovery and cardiac rhythm, after completion of dosed physical exercises. Furthermore, the influence of such exercises on professional field hockey players general and special physical preparedness is being presented in the mentioned investigation. It is established that the application of the endogenous-hypoxic breathing technique in the field hockey players` training process promotes their general and special physical preparedness, improves sportsmen`s functional efficiency regarding the body aerobic and anaerobic productivity rates and the external respiratory apparatus functional possibilities, as well as promotes adaptation to hypoxia and accelerates the body`s restorative processes.